SOIL QUALITY MONITORING PROTOTYPE WITH HUMIDITY AND TEMPERATURE PARAMETERS FOR PADDY PLANTS - Susilawati Susilawati; Iqbal Maulana (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2020)
Paddy is one of the most important plants in Indonesia because most of the Indonesian main food is rice. Paddy productivity can be increased by utilizing technological development. This study aims to design and make a measurement tool for soil temperature and humidity in paddy fields in the Karawang regency. This measurement tool uses Arduino mega and several sensors, the DS18B20 sensor which functions as a ground temperature sensor. Grove moisture sensor that functions as a sensor to detect soil moisture. Information for the value of these parameters will be listed on the LCD that has been installed. Data was collected in the paddy fields of Telukjambe sub-district, Karawang Regency, data collection was carried out with a depth of 2 cm and a depth of 4 cm. At a depth of 4 cm, the temperature and humidity parameters are stable, while at a depth of 2 cm the temperature parameter is stable while the humidity is unstable, and the best humidity value is at a depth of 4 cm.